Approximating Common Fixed Points of Nonspreading-Type Mappings and Nonexpansive Mappings in a Hilbert Space - Kyung Soo Kim (Abstract and Applied Analysis)
We obtain some fundamental properties for k-strictly pseudo-nonspreading mappings in a Hilbert space. We study approximation of common fixed points of k-strictly pseudo-nonspreading mappings and nonexpansive mappings in a Hilbert space by using a new iterative scheme. Furthermore, we suggest some open problems.